Australian species of the ant genus Dolichoderus (Hymenoptera: Formicidae) - Shattuck, Steven O.; Marsden, Sharon (Zootaxa, 2013)
The Australian species of the ant genus Dolichoderus are revised. The fauna contains 27 species belonging to four species groups, the australis group (5 species, 2 newly described), the doriae group (6 species, 2 newly described), the scabridus group (6 species, 1 newly described) and the scrobiculatus group (10 species, 4 newly described). The former subspecies niger Crawley and rufotibialis Clark are raised to species-level. The following nine new species are described: albamaculus sp. n., canopus sp. n., etus sp. n., gordoni sp. n., inferus sp. n., kathae sp. n., omicron sp. n., rutilus sp. n. and semiorbis sp. n. Four new synonyms are proposed: armstrongi McAreavey with reflexus Clark, glauerti Wheeler with parvus Clark, occidentalis Clark with formosus Clark and ruficornis Santschi with scabridus Roger. A neotype is designated for D. clusor Forel. The majority of species are found in southern forested areas with only a few species known from arid and tropical regions.